First Aid Education for High School Students - Focusing on CPR, AED installation and application - Choi, Sun-Ha; Kim, Seong-Yeon (International JOURNAL OF CONTENTS, 2011)
This research, by analyzing the current first aid education status in K district, Seoul and comparing first aid education systems in other developed countries, introduces the need of first aid/Cardio Pulmonary Resuscitation(CPR) education with Automated External Defibrillator(AED) usage to high school students, who are on the verge of becoming adults. The thorough research shows that schoolsshould be appointed as mandatory facilities for AEDs by laws and execute first aid education to their students. Only through organized and consistent first aid education would the students develop into true volunteers who not only have altruistic minds, but the ability to fluently adapt to medical emergency and properly use AED. In addition, the research also outlines various laws that could be legislated such as having to master the basic degrees of first aid education before getting driver’s license and graduating high school so that more people become aware of first aid. KCI Citation Count: 0